THE ROLE OF PHYSICAL CULTURE AND SPORTS IN STUDENT ACTIVITY AND LIFESTYLE - Arabboyev Qahramon Tohirjonovich; Tohirjonov Hojiakbar Qahramon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article talks about the theoretical foundations of the need for physical education and sports for students of higher educational institutions. It is also written about the uniqueness of educational and sports activities of physical education students.